2002
DOI: 10.1002/bip.10190
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies of starches with different water contents

Abstract: Abstract:The proportion of double helices in starches from a series of pea [rb, rug4-b, rug3-a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(52 citation statements)
references
References 33 publications
(72 reference statements)
5
46
1
Order By: Relevance
“…Compared to the obvious increase in the enthalpy of starch after annealing (Table 1), the changes in double-helix content and relative crystallinity are less obvious. The lack of significant correlation between results of calorimetry and NMR observations is consistent with previous findings (Bogracheva, Wang, Wang, & Hedley, 2002), which suggested that different molecular structures were probed by DSC and NMR spectra. While high-resolution solid-state NMR gives characteristic spectra for ordered helices and non-ordered chains (Gidley & Bociek, 1985;Gidley et al, 1995), DSC is believed to observe on the overall enthalpy change involved in the melting of the hydrogen bonds of crystallites but also the dissociation of the hydrogen bonds of double helices (Tananuwong & Reid, 2004).…”
Section: Article In Presssupporting
confidence: 92%
“…Compared to the obvious increase in the enthalpy of starch after annealing (Table 1), the changes in double-helix content and relative crystallinity are less obvious. The lack of significant correlation between results of calorimetry and NMR observations is consistent with previous findings (Bogracheva, Wang, Wang, & Hedley, 2002), which suggested that different molecular structures were probed by DSC and NMR spectra. While high-resolution solid-state NMR gives characteristic spectra for ordered helices and non-ordered chains (Gidley & Bociek, 1985;Gidley et al, 1995), DSC is believed to observe on the overall enthalpy change involved in the melting of the hydrogen bonds of crystallites but also the dissociation of the hydrogen bonds of double helices (Tananuwong & Reid, 2004).…”
Section: Article In Presssupporting
confidence: 92%
“…This result suggests that, during hydration, a proportion of non-crystalline starch helices organized into crystal cells with the water molecules via hydrogen bonds, which led to an increased quantity of the starch crystallites. Previous studies confirmed similar information that the increased moisture content contributed to the growing crystallinity of starch [28,29].…”
Section: Fig 3b)supporting
confidence: 79%
“…3b), the A-type crystallization peaks disappeared, only two weak crystallization peaks were detected at 2Â = 14 • and 21 • which were the characteristic peaks of V-type [30]. Besides, an amorphous dispersion band was found at 2Â = 19 • [31]. The crystallization type of native starch changed and the amorphous regions increased after its esterification of MA, indicating that the esterification reaction happened not only in the amorphous areas but also in the crystalline areas of starch, thus the crystal structure of native starch was significantly destroyed.…”
Section: The Xrd Analysis Of Tpsmentioning
confidence: 89%